2019
DOI: 10.1002/cbin.11108
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in chemical carriers of proteins and peptides

Abstract: The successful intracellular delivery of biologically active proteins and peptides plays an important role for therapeutic applications. Indeed, protein/peptide delivery could overcome some problems of gene therapy, for example, controlling the expression levels and the integration of transgene into the host cell genome. Thus, protein/peptide drug delivery showed a promising and safe approach for treatment of cancer and infectious diseases. Due to the unique physical and chemical properties of proteins, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 113 publications
(252 reference statements)
0
16
0
Order By: Relevance
“…A particular focus for these drugs has been the development of delivery systems based on nanoparticles (NPs) of poly(lactide- co -glycolide) [ 15 , 16 ] and chitosan [ 17 ], as well as different poly(methacrylic acid) microgels [ 18 ]. Summaries of different delivery systems available for antibacterial peptide drugs have been presented in some recent reviews [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A particular focus for these drugs has been the development of delivery systems based on nanoparticles (NPs) of poly(lactide- co -glycolide) [ 15 , 16 ] and chitosan [ 17 ], as well as different poly(methacrylic acid) microgels [ 18 ]. Summaries of different delivery systems available for antibacterial peptide drugs have been presented in some recent reviews [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that ACBP combined with oxaliplatin significantly inhibits proliferation of MKN-45 cells ( 35 ). Recently, the replacement of peptides with chemical modifications to achieve the same therapeutic effects as their natural peptide counterparts in combined chemotherapeutics has been developed ( 55 ). Furthermore, the incorporation of the Se atom into amino acids and peptides is primarily restricted to selenocysteine derivatives ( 56 ) and there is a need to develop synthesis of amino acid-derived chiral Se compounds for evaluation of antioxidant, antihypertensive, anti-inflammatory and immunomodulatory effects ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, peptides ligands can be optimized for targeting by combining the phage display-based selection with the computational modeling of peptide structure. The peptide optimization can be achieved by chemical modifications that increase their affinity, avidity, target specificity, and water solubility [70].…”
Section: Optimization Of Peptides For Targetingmentioning
confidence: 99%